Abundance and Distribution of Microbial Cells and Viruses in an Alluvial Aquifer - Pan, Donald; Nolan, Jason; Williams, Kenneth H.; Robbins, Mark J.; Weber, Karrie A. (Frontiers in Microbiology, 2017)
Viruses are the most abundant biological entity on Earth and their interactions with microbial communities are recognized to influence microbial ecology and impact biogeochemical cycling in various ecosystems. While the factors that control the distribution of viruses in surface aquatic environments are well-characterized, the abundance and distribution of continental subsurface viruses with respect to microbial abundance and biogeochemical parameters have not yet been established. In order to begin to understand the factors governing virus distribution in subsurface environments, we assessed microbial cell and virus abundance in groundwater concurrent with groundwater chemistry in a uranium impacted alluvial aquifer adjoining the Colorado River near Rifle, CO. Virus abundance ranged from 8.0 × 104 to 1.0 × 106 mL−1 and exceeded cell abundance in all samples (cell abundance ranged from 5.8 × 104 to 6.1 × 105 mL−1). The virus to microbial cell ratio ranged from 1.1 to 8.1 and averaged 3.0 ± 1.6 with virus abundance most strongly correlated to cell abundance (Spearman's ρ = 0.73, p < 0.001). Both viruses and cells were positively correlated to dissolved organic carbon (DOC) with cells having a slightly stronger correlation (Spearman's ρ = 0.46, p < 0.05 and ρ = 0.54, p < 0.05; respectively). Groundwater uranium was also strongly correlated with DOC and virus and cell abundance (Spearman's ρ = 0.62, p < 0.05; ρ = 0.46, p < 0.05; and ρ = 0.50, p < 0.05; respectively). Together the data indicate that microbial cell and virus abundance are correlated to the geochemical conditions in the aquifer. As such local geochemical conditions likely control microbial host cell abundance which in turn controls viral abundance. Given the potential impacts of viral-mediated cell lysis such as liberation of labile organic matter from lysed cells and changes in microbial community structure, viral interactions with the microbiota should be considered in an effort to understand subsurface biogeochemical cycling and contaminant mobility.